Reliable, Real-Time Routing in Wireless Sensor and Actuator Networks. (9th January 2011) - Krogmann, Martin; Heidrich, Mike; Bichler, Daniel; Barisic, Daniel; Stromberg, Guido
Abstract : We present a novel Reliable, Real-time Routing protocol (3R) based on multipath routing for highly time-constrained Wireless Sensor and Actuator Networks (WSANs). The protocol consists of a newly designed routing metric and a routing algorithm utilizing this metric. Our routing metric enables strong Quality-of-Service (QoS) support based on parallel transmissions which significantly reduces transmission delays in WSANs. A routing algorithm utilizing this metric is presented based on Dijkstra's shortest path. A novel Medium Access Control (MAC) layer that supports dynamical adjustments of retransmission limits, reduces traffic overhead in multipath routing protocols. Thorough simulations have been performed to evaluate the routing protocol, and the results show that real-time performance of WSANs can be vastly improved.